The use of supplementary materials in EFL classes: A comparative analysis of public and private senior high schools, study done in 13 de Mayo high school located in Portovelo canton and San Juan Bosco high school from Zaruma canton during 2011- 2012 school year - Macas Aguilar, Nancy del Carmen (2013)
The present study focuses the use of supplementary materials in EFL classes: “A comparative analysis of public and private senior high schools,” which purpose is to analyse supporting materials used in EFL classes according to pertinence, appropriateness, and quality. Therefore, to develop this research, it was necessary to select two senior high schools as a sample to collect information. The first one is a Public senior high school located in Portovelo canton, and the other one is a Private senior high school located in Zaruma canton. A group of 115 students in total from first, second, and third years of the both senior high schools were chosen to observe five classes in each year according to real situations with respect to the use of supplementary materials. Once identified the sample, the data collected was tabulated using different techniques, instruments and resources. Then, these data was analyzed and compared applying the qualitative and quantitative methods. Finally, the results showed that in the public senior high school the use of supplementary materials is less frequent than in the private senior high school